Sperm retrieval and intracytoplasmic sperm injection outcomes in men with cystic fibrosis disease versus congenital bilateral absence of the vas deferens - J Abram McBride; Taylor P Kohn; Daniel J Mazur; Larry I Lipshultz; R Matthew Coward (Asian Journal of Andrology, 2021)
Recent data suggest that cystic fibrosis transmembrane conductance regulator (CFTR) gene alterations negatively impact male fertility beyond obstruction. We sought to compare gene alterations, sperm retrieval rates, and intracytoplasmic sperm injection (ICSI) outcomes among men with cystic fibrosis (CF) disease and congenital bilateral absence of the vas deferens (CBAVD) only. We retrospectively evaluated all men who underwent surgical sperm retrieval at two academic, high-volume andrology centers from 2010 to 2018. Only men with documented CFTR alterations and obstructive azoospermia from either CBAVD or CF were included. Differences between groups for CFTR abnormality, sperm retrieval, and ICSI outcomes were statistically analyzed. Overall, 39 patients were included with 10 in the CF and 29 in the CBAVD groups. Surgical sperm retrieval rates were significantly lower in the CF group for sperm concentration (14.8 × 10[6] ml-1 vs 61.4 × 10[6] ml−1, P = 0.02) and total motile sperm count (2.9 million vs 11.4 million, P = 0.01). This difference was only predicted by homozygous delta F508 CFTR mutations (P < 0.05). The CF group also demonstrated a significantly higher rate of rescue testicular sperm extraction (70.0% vs 27.6%, P < 0.03) and lower fertilization rate with ICSI (32.5% vs 68.9%, P < 0.01). In conclusion, those with CF demonstrated lower sperm quality, greater difficulty with sperm retrieval, and worse ICSI outcomes compared with CBAVD-only patients. Homozygous delta F508 CFTR mutations appear to significantly impair spermatogenesis and sperm function.